Joint channel estimation and ISI/ICI cancellation for MIMO?OFDM systems. (14th March 2011) - Chiu, Yi-Jen; Chen, Chien-Sheng; Chang, Ting-Wei
In MIMO?OFDM systems, the multipath components whose delays exceed Cyclic Prefix cause Inter-Symbol Interference and Inter-Carrier Interference, which may degrade system performance severely. In this paper, we propose a joint channel estimation and ISI/ICI cancellation scheme in which a limited CP is used in a trade-off against high-rate performance in MIMO?OFDM systems. A channel estimation scheme based on the criterion of Expectation-Maximisation (EM) algorithm can be proposed through the use of a training symbol. Simulation results show that the proposed method can significantly enhance the overall MIMO?OFDM system performance after only a few iterations.